A framework for an integrated nuclear digital environment. (March 2016) - Patterson, Eann A.; Taylor, Richard J.; Bankhead, Mark
Abstract: A conceptual framework is proposed for a digital environment extending from the prototype design of nuclear plants through operations and decommissioning to storage and waste disposal. The environment consists of a series of interconnected multi-scale, multi-physics computational models linked to the real-world by data acquired during validation of prototypes, in-service monitoring and inspections of plant, post-shut-down inspections of plant and in-situ monitoring of stored waste. The technology gaps for the implementation of the integrated nuclear digital environment (INDE) are identified and discussed together with the advantages to be gained from its implementation. Implementation of INDE will be dependent on future advances in High Performance Computing systems approaching the exascale and parallel advances in the development of algorithms for processing large amounts of data. The data itself will be acquired through innovations in measurement, analysis and uncertainty and will be applied through projects relating to lifetime extension, decommissioning and resurgent national science programmes. It is postulated that the existence of this type of framework might be inevitable given both nuclear-specific and non-nuclear drivers and may be essential for the nuclear industry to deliver current and future challenges from the clean-up of legacy waste sites to time and budget, future generation nuclear reactors and small-scale mass-production of modular nuclear power plants. It is proposed that implementation of INDE will lead to shorten development times, reduced costs and increased credibility, operability, reliability and safety. Graphical abstract: Highlights: A process for creating an integrated digital environment for a plant life-cycle. Integration of multi-scale, multi-physics models in HPC with real-world data. Identification of technology gaps and a knowledge management framework. Implementation has the potential to reduce development times and costs. INDE would increase credibility, operability, reliability & safety of nuclear plant.